Death from Penetrating Trauma to the Chest and Abdomen - Asan Petrus (JURNAL PANDU HUSADA, 2023)
Abstract: Deaths from penetrating trauma are less common than blunt trauma, gunshot wounds, asphyxia and drug intoxication. The most common mode of death is homicide. Penetrating trauma to the chest and abdomen causes severe bleeding and damage to internal organs, leading to instability of vital signs. Hypovolemic shock due to loss of circulating volume causes tissue hypoperfusion and hypoxia, if not treated promptly will cause multi-organ failure and death. The objectives of this case are to review cases of penetrating trauma to the chest and abdomen in forensic and medicolegal aspects. This case reports a victim of penetrating trauma by a sharp wound who was found dead in the direction of a palm oil plantation not far from his house. In this case, the stab wound to the abdomen was the most harmful to the victim as it caused severe bleeding (1400 mL) and was aggravated by bleeding from the stab wound to the chest (750 mL). The bleeding resulted in a loss of blood volume of more than 40% of the total blood in the victim's body. The victim experienced hypovolemic shock with decreased systolic blood pressure, tachycardia, and oliguria. As a result, oxygen delivery to vital organs cannot meet oxygen demand, causing a drop in blood pressure, refractory acidosis, and a further drop in cardiac output, leading to multiorgan failure (MOF) and, finally, death. The victim's death was unnatural and the cause of death was due to sharp trauma in the form of a stab wound to the abdomen that penetrated the abdominal cavity aggravated by a stab wound to the left chest resulting in severe bleeding. As per the Indonesian Criminal Code, Article number 338 or 340, the offender of this murder can be sentenced.